FcγRIIB functions as an IgG transporter in the mammary gland - Xin Li; Lijuan Du; Zihui Wan; Zhiren Jin; Yuanhao Peng; Yongliang Fan; Cuncun Ke; Yonghe Ma; Haitang Han; Shuyang Yu; Gengsheng Cao; Tian Huang; et al. (Proceedings of the National Academy of Sciences, 2026)
In mammals, passive acquisition of maternal immunoglobulins is essential for neonatal immune development and defense against infections. IgG, a central mediator of humoral immunity, is maternally transferred via distinct mechanisms depending on placental structure in placental mammals. In humans (hemochorial placenta), IgG is prenatally transported across the placenta, whereas in large domestic animals such as pigs and cows (epitheliochorial/connective chorionic placenta), IgG is exclusively transferred postnatally via colostrum and absorbed in the neonatal intestine. Rodents (allantoic chorionic placenta) employ both pathways. Critically, IgG must traverse multiple tissue barriers-including the placenta, mammary gland, and neonatal intestine-to reach the circulation of newborns. While FcRn is known to facilitate IgG transport in the placenta and neonatal intestine, the mechanisms underlying IgG secretion into milk remain unclear. Here, we identify FcγRIIB as the key transporter mediating maternal IgG transfer across the mammary gland in mammals. Using constitutive and conditional knockout mice, we demonstrate that FcγRIIB deficiency impairs mammary IgG transfer, whereas its overexpression enhances milk IgG levels. Strikingly, in pigs, FcγRIIB is highly upregulated in mammary tissue prepartum, and its disruption abolishes IgG accumulation in colostrum. Our work opens avenues for improving neonatal immunity through targeted modulation of FcγRIIB-mediated IgG transport.